Expression of Concern Notice: Basketball Anterior and Posterior Portal Veins Doppler Imaging of Sports Medicine Technique Exploration - Zhu, Wei (EAI Endorsed Transactions on Pervasive Health and Technology, 2026)
We, the publisher, are issuing an expression of concern about Wei Zhu (2024) Basketball Anterior and Posterior Portal Veins Doppler Imaging of Sports Medicine Technique Exploration. https://doi.org/10.4108/eetpht.10.5152 There is a concern over the integrity of the peer review review process and suspected manipulation of the editorial process. The investigation is ongoing and we advise scholars to exercise caution when referencing this manuscript.